Mathematical Ideograms and their Virtual Teaching using Algebrator Software for Regular Basic Education (SCIÉNDO INGENIUM, 2023)
This paper presents a study regarding mathematical ideograms and the use of the mathematical software Algebrator, with the purpose of recommending its management in regular basic education (EBR). In particular, this analysis is aimed at describing the Algebrator software as a technological tool and implementing its use in solving algebraic problems, favoring student learning, especially in educational cycles VI – VII. On the other hand, we will describe the efficiency of the software and its specific role to implement the ideogram in mathematics and therefore its use of both in educational institutions, motivating the use of new learning strategies at the service of virtual teaching in mathematics. Undoubtedly, the application of mathematical software of these characteristics is a challenge in educational institutions, proving necessary in the face of the advancement of the knowledge society. In this scenario, Algebrator favors education in its virtual modality as a training and motivating means of teaching – learning within the educational community, proving ideal to achieve positive results in new generations of students.
Keywords: Mathematical software; Algebrator; Educational Software; Mathematical ideogram